2012
DOI: 10.1007/s12010-012-9689-5
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies on the Product Inhibition of Enzymatic Lignocellulose Hydrolysis

Abstract: In order to understand the product inhibition of enzymatic lignocellulose hydrolysis, the enzymatic hydrolysis of pretreated rice straw was carried out over an enzyme loading range of 2 to 30 FPU/g substrate, and the inhibition of enzymatic hydrolysis was analyzed kinetically based on the reducing sugars produced. It was shown that glucose, xylose, and arabinose were the main reducing sugar components contained in the hydrolysate. The mass ratio of glucose, xylose, and arabinose to the total reducing sugars wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…, it would be sugars in the whole pretreated slurry that resulted in the lower efficiency of enzymatic saccharification. Because, it has been reported that the sugar derivations from glucan and xylan dramatically decrease efficiency of enzymatic saccharification . However, pretreatment at higher temperature or with lower solid load resulted in higher efficiency of enzymatic saccharification (Figure B).…”
Section: Resultsmentioning
confidence: 97%
“…, it would be sugars in the whole pretreated slurry that resulted in the lower efficiency of enzymatic saccharification. Because, it has been reported that the sugar derivations from glucan and xylan dramatically decrease efficiency of enzymatic saccharification . However, pretreatment at higher temperature or with lower solid load resulted in higher efficiency of enzymatic saccharification (Figure B).…”
Section: Resultsmentioning
confidence: 97%
“…However, the low increase in glucose concentration and almost constant level of cellobiose after the first 6 h suggests that b-glucosidase activity was inhibited by glucose. Inhibition of cellobiohydrolases (EC 3.2.1.91) and endoglucanases (Andrić et al 2010;Miao et al 2012). To overcome this problem, enzymatic hydrolysis processes are either conducted in Tables 4 and 5 were correlated with apparent changes in the appearance of fibers contained in the poplar pulp, which was digested by the preparation NS-22086.…”
Section: Selection Of Enzyme Preparationmentioning
confidence: 99%
“…Product release from enzyme active sites is often reversible and rebinding is common in many enzyme systems1234. Liberated product(s) can effectively compete with substrate binding to enzyme active sites and inhibit enzyme cycling.…”
mentioning
confidence: 99%